Opportunities and Challenges for Pastoral Beef Cattle Production in Ethiopia - Belete Kuraz Abebe; Mulugeta Tesfaye Alemayehu; Sharew Mekonnen Haile (Advances in Agriculture)
The beef cattle production sector plays a crucial role in the livelihoods of pastoral farmers in Ethiopia, and it is the main source of beef animals for domestic and foreign markets. As compared to other African countries, Ethiopia has a huge beef cattle population (65.35 million heads). However, the quality and quantity of beef, as well as per capita meat consumption of Ethiopians, are very low (8.4 kg/individual/year). In this sense, the goal of this review was to provide and synthesize the most validated scientific information on the opportunities and challenges for pastoral beef cattle production in Ethiopia. The potential for pastoral beef cattle producers in Ethiopia included population growth, urbanization, literacy, and family income, as well as high demand for beef animals in domestic and foreign markets. In contrast, problems with beef cattle production systems, diseases, shortages of feed and water, lack of veterinary services, droughts, lack of market access and infrastructure, illegal animal trades, and poor genetic potential of indigenous cattle are among the limiting factors that hamper efficient beef production in the country. In Ethiopia, the yield and compositional quality of beef are very low compared to other African countries and the global market in general. Therefore, empowering pastoral beef cattle producers will help us to supply high quality and quantity of beef and will ensure sustainable beef cattle production with an identified market destination and access.